q-deformed variational study of the Lipkin-Meshkov-Glick model via coherent states - Avancini, S. S. [UNESP]; Brunelli, J. C. [UNESP] (Elsevier, 1993)
We show that the ground-state energy of the q-deformed Lipkin-Meshkov-Glick Hamiltonian can be estimated by q-deformed coherent states. We also use these coherent states to analyse qualitatively the suppression of the second order ground-state energy phase transition of this model. © 1993.